2016
DOI: 10.1111/opo.12288
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation of anterior scleral and conjunctival thickness

Abstract: This study provides the first evidence of diurnal variations occurring in the thickness of the anterior sclera and conjunctiva. Studies requiring precise measures of these anatomical layers should therefore take time of day into consideration. The majority of the observed changes occurred in the early morning immediately after waking and were of larger magnitude in the conjunctiva compared to the sclera. Thickness changes at other times of the day were of smaller magnitude and generally not statistically signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 38 publications
5
40
1
Order By: Relevance
“…The Huynh and Feld adjustment is similar but is regarded as more liberal than Greenhouse and Geisser. When search terms were used to specifically identify those articles which tested and corrected for sphericity, 14/66 (21%) used Mauchly's test, 24 47/66 (71%) the Greenhouse-Geisser correction, [25][26][27] and 5/66 (8%) the Huynh and Feld correction, 28 62% of which were published in the period 2012 to the present. A problem with these procedures, however, is that they may not protect against multiple testing using post-hoc tests after RM-ANOVA especially if an overall error term is used.…”
Section: Resultsmentioning
confidence: 99%
“…The Huynh and Feld adjustment is similar but is regarded as more liberal than Greenhouse and Geisser. When search terms were used to specifically identify those articles which tested and corrected for sphericity, 14/66 (21%) used Mauchly's test, 24 47/66 (71%) the Greenhouse-Geisser correction, [25][26][27] and 5/66 (8%) the Huynh and Feld correction, 28 62% of which were published in the period 2012 to the present. A problem with these procedures, however, is that they may not protect against multiple testing using post-hoc tests after RM-ANOVA especially if an overall error term is used.…”
Section: Resultsmentioning
confidence: 99%
“…The special issue also emphasised fundamental research questions that can be addressed with imaging. These included diurnal changes in ocular tissues, 5 the use of imaging to understand and diagnose retinal disease 3,6,7 and the extent to which the brain changes its structure and function in individuals with macular degeneration or glaucoma. 8,9 In addition, contemporary themes in vision science imaging research were identified by two invited review papers featured within the special issue.…”
mentioning
confidence: 99%
“…Two of the participants were soft contact lens wearers, but they ceased lens wear one week prior to participation in the experiment and did not wear lenses for the duration of their involvement in the experiment. To limit the potential confounding influence of ocular diurnal variations upon the results (Read et al, 2016b), all three experimental conditions were tested at approximately the same time of day between 9 am and 2 pm on different days, in randomized order, for each subject.…”
Section: Methodology 121 Subjectsmentioning
confidence: 99%
“…Several studies have reported the Schlemm's canal lumen to be larger nasally, compared to the temporal region (Kagemann et al, 2010;Day et al, 2013;Li et al2016), while other studies did not find a significant difference between nasal and temporal sides of Schlemm's canal (Shi et al, 2012) or they reported the temporal cross-sectional area of Schlemm's canal to be larger than the nasal Schlemm's canal . In contrast, there have been fewer of studies on anterior scleral thickness (Oliveira et al, 2006;Mohamed-Noor et al, 2009;Yoo et al, 2011;Ebneter et al, 2015;Read et al, 2016a;Read et al, 2016b). These studies The number of studies reporting the thickness of the conjunctival stroma/episclera complex is even fewer, with only a small number of studies reporting the estimated average thickness of conjunctival stroma/episclera complex to be 197.7 ± 32.5 μm in a population of 711 healthy Chinese subjects (age from 8-85 years) , 249 ± 59 μm in a population of 111 healthy Caucasian subjects (age from 10-31 years) (Read et al, 2016b) and 255 ± 10 μm in population of 10 healthy adult subjects (age from 21-33 years) (Alonso-Caneiro et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation